The Role of Teachers in Developing Students’ Science Creative Thinking Skills in Jordan and Sultanate of Oman - Hamad Al-Yahmadi; Sameera Al-Shorman (RIRAI Publisher, 2022)
The study aimed to identify the degree to which science teachers developed school students’ creative thinking skills in Jordan and Sultanate of Oman. It also aimed to find out if the teachers’ role in developing school students’ creative thinking skills differed as per their work place (Jordan and Oman) and whether or not there were statistically significant differences at the significance level (0.05=α) in the teachers’ role in developing school students’ creative thinking skills from the perspective of teachers attributed to the variable of teaching experience. To achieve the study objectives, the descriptive survey approach was used through developing a questionnaire with 31 statements which was distributed to a sample of 140 teachers teaching science to grades 4 to 8 in public schools in Jordan and Sultanate of Oman in the academic year 2021 – 2022. 5- point Likert scale was used to analyze the data collected. The findings showed that primary education science teachers practiced creative thinking skills with their students to a high degree as the mean of their responses to the questionnaire statements was 3.43 with a standard deviation 1.12. There were no statistically significant differences in the science teachers’ response means in Jordan and Oman. However, there were statistically significant differences at the significance level (0.05=α) in the teachers’ response means in favor of the female teachers whose response mean was 4.25 which was higher than the male teachers’ response mean which was 3.35. This result might be attributed to a number of factors such as women in Arab societies try to prove themselves and try to prove that they are more distinguished than men. In light of the findings, the study recommended adopting teaching strategies that develop students’ creative thinking skills, supporting teachers who develop these skills and generalizing these findings to other educational stages.